Case report: Fatal co-infection-melioidosis and leptospirosis - How, Soon Hin; Ramalingam, Rajalingam; Kuan, Yeh Chunn; Ahmad, Norazah; Ab Rahman, Jamalludin; Mohamed, Mohd Sapian (American Society of Tropical Medicine and Hygiene, 2012)
Co-infection of melioidosis and leptospirosis is uncommon. We report here four such cases, confirmed by blood culture for melioidosis and blood polymerase-chain reaction for leptospirosis, which occurred among rescuers involved in a search and rescue operation for a young man who was suspected to have drowned in Lubuk Yu, a recreational forest in Pahang, Malaysia. Despite treatment, three of the patients died from the co-infection.